The Effectiveness of the KTP-el Service at the Population and Civil Registry Office of Parepare City - Setyawati, Iin; Nasrullah, Muh; Salam, Rudi (Universitas Negeri Makassar, 2019)
Public services are implemented to provide satisfaction for service users whose implementation requires the principles of service. This study aims to determine the effectiveness of the KTP-el service at the Population and Civil Registry Office of Parepare City. This research uses a qualitative descriptive approach with 8 informants. Data collection uses observation, interview and documentation techniques. While the data analysis technique used consists of four ways, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the effectiveness of the KTP-el service at the Population and Civil Registry Office of Parepare City, is in the quite effective category. This is demonstrated through the focus of research that service procedures are in the effective category, employee discipline is in the effective category, fairness of service delivery is in the quite effective category, the reasonableness of cost is set effectively, service convenience is in the quite effective category.